Recruitment and Use of Child Soldiers in Afghanistan: Cultural Traits as Pivotal Factor - Ghulam Mohammad Qanet; Mohammad Shekaib Alam; Mohammad Naqib Ishan Jan (Journal of Islamic World and Politics, 2021)
This paper explores the cultural values that prevailed in Afghanistan to understand the recruitment and use of underage soldiers in the long-lasting armed conflict while comparing the existing domestic and international law. The study analyzed the effect of the traditions of Afghans on child soldiering. The method was doctrinal, and therefore, the collected and analyzed data was qualitative. The analysis was thematical, where each related idea was subjected to review and evaluation. The research found that since time immemorial, the Afghan culture traditions were conducive to underage soldiering for various reasons, including peace and justice where male and female child warriors are treated as heroes, perhaps more than any other member of the Afghan society. Due to the stated reasonings, the study established that more underage soldiers were used and recruited during the period of the British Empire, Soviet invasion of Afghanistan, and the civil war that caused the Taliban and Northern Alliance to resume control and in the post 9/11 phase of armed conflict in Afghanistan irrespective of domestic and international law that prohibited the recruitment and use of underage soldiers as it violated their basic fundamental rights of childhood.